If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 7 = 7y + 3 + 3y + -7 Reorder the terms: 7 + 9y = 7y + 3 + 3y + -7 Reorder the terms: 7 + 9y = 3 + -7 + 7y + 3y Combine like terms: 3 + -7 = -4 7 + 9y = -4 + 7y + 3y Combine like terms: 7y + 3y = 10y 7 + 9y = -4 + 10y Solving 7 + 9y = -4 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. 7 + 9y + -10y = -4 + 10y + -10y Combine like terms: 9y + -10y = -1y 7 + -1y = -4 + 10y + -10y Combine like terms: 10y + -10y = 0 7 + -1y = -4 + 0 7 + -1y = -4 Add '-7' to each side of the equation. 7 + -7 + -1y = -4 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = -4 + -7 -1y = -4 + -7 Combine like terms: -4 + -7 = -11 -1y = -11 Divide each side by '-1'. y = 11 Simplifying y = 11
| 68=(1063)(149/360)r | | 2x+10-6x=-22 | | 3x+2y-2z=2 | | -2z^2+15=-21 | | 54+9h=225 | | 16.3k+19.2+7.5k=-63.1 | | 4x^6+x^3-6x^2-x^2+5= | | 31=2x+(2x-1) | | -6+6x-2x=14 | | (7r+5)(2r-6)=0 | | (4-5i)/(5-1) | | 2z+13=8z+1 | | 2x-1+x=-28 | | 9y+8=6y+1 | | X+4-3=6*5 | | 2-x+6x=37 | | 42=(960)(177/360)r | | 4x+5ys=12 | | y+(-2)=100 | | 15+x=2x+6 | | -13=2x+5x+8 | | 71+[-5+(-2x+3)]=25-[-(3x+4)-(4x+3)] | | 5(p+2)+6(-3-p)=0 | | 7x^2-11x+5=0 | | 4x^2-80x+144=0 | | 4+6x+2x=76 | | 1+[-5+(-2x+3)]=25-[-(3x+4)-(4x+3)] | | y=7x+-10+-3 | | 5p^2-125=0 | | -3x+7-4x=-77 | | x+x+2+x+4=66-x | | 315=30z |